Pelatihan Teknik Metafora untuk Meningkatkan Efisiensi Proses Konseling di SMK Negeri 5 Malang - Diniy Hidayatur Rahman; Devy Probowati; Widya Multisari; Sausanuz Zakiyyah Hamibawani; Arifah Wulandari; Khusnul Khowatim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This training was held with the aim of increasing the competency of counselors at SMK Negeri 5 Malang in using metaphor techniques in counseling. By increasing counselor competency in using metaphor techniques, it is hoped that counseling services at SMK Negeri 5 Malang can run better and more efficiently. This community service activity will be carried out in the form of training using the flipped classroom model and experiential learning. The flipped classroom model is used to help participants master the concepts and procedures of metaphor techniques in counseling. Meanwhile, experiential learning is used to improve participants' skills in applying metaphor techniques in counseling. This training was carried out by three lecturers at the Department of Guidance and Counseling, State University of Malang and attended by seven counselors at State Vocational School 5 Malang. The training was carried out in three sessions. The first session was held online asynchronously. In this session, participants are asked to study the material independently through the guides and training materials that have been provided. The second training session was carried out online synchronously. In this session, participants were invited to discuss and explore the concept of metaphor that had been studied independently in the first session. In the third session, participants were invited to practice knowledge about metaphors in counseling sessions. Measurements after the training activities showed that there was an increase in the participants' post-test scores compared to the pre-test scores. Based on interviews with participant representatives, it was also known that the participants had a positive impression of all training activities.